2020
DOI: 10.1093/ehjci/ehaa946.1012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the relative apical sparing pattern of longitudinal strain in patients with cardiac amyloidosis

Abstract: Background The relative apical sparing pattern (RASP) of left ventricular (LV) longitudinal strain (LS) is frequently associated with cardiac amyloidosis (CA). However, some patients with CA do not show the RASP, and their clinical characteristics have not been fully clarified. We sought to investigate the clinical significance of RASP in patients with CA. Methods One hundred consecutive CA patients who were diagnosed by biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A further echocardiogram showed marked hypertrophy (interventricular septal thickness: 20 mm, posterior wall of left ventricle: 14 mm) with slightly reduced pump function (EF 45%), signs of increased filling pressure and a severe reduction of longitudinal deformation indices (global longitudinal strain, GL2D-strain: −6.2%), with an “apical sparing pattern” specific for cardiac amyloidosis ( Figure 1A and B ). 23 Under a clinical suspect of AL amyloidosis and considering the underlying MGUS, a biopsy of the iliac crest bone marrow was performed, which ruled-out the presence of amyloid, as well as of lymphoma or multiple myeloma. At this point, a Congo red histochemical investigation and polarized light test performed on abdominal fat tissues showed the presence of amyloid; however, no immunofluorescence typing was performed.…”
Section: Case Reportsmentioning
confidence: 99%
“…A further echocardiogram showed marked hypertrophy (interventricular septal thickness: 20 mm, posterior wall of left ventricle: 14 mm) with slightly reduced pump function (EF 45%), signs of increased filling pressure and a severe reduction of longitudinal deformation indices (global longitudinal strain, GL2D-strain: −6.2%), with an “apical sparing pattern” specific for cardiac amyloidosis ( Figure 1A and B ). 23 Under a clinical suspect of AL amyloidosis and considering the underlying MGUS, a biopsy of the iliac crest bone marrow was performed, which ruled-out the presence of amyloid, as well as of lymphoma or multiple myeloma. At this point, a Congo red histochemical investigation and polarized light test performed on abdominal fat tissues showed the presence of amyloid; however, no immunofluorescence typing was performed.…”
Section: Case Reportsmentioning
confidence: 99%
“…However, the incidence of relative apical sparing has proven to be low in case of mild LVH, thus this pattern may be less useful as a red flag in the early presentation 98 . Eventually, the apical sparing pattern may be seen in other infiltrative cardiomyopathies like Fabry disease 99 …”
Section: Echocardiographymentioning
confidence: 99%
“…97 However, the incidence of relative apical sparing has proven to be low in case of mild LVH, thus this pattern may be less useful as a red flag in the early presentation. 98 Eventually, the apical sparing pattern may be seen in other infiltrative cardiomyopathies like Fabry disease. 99 Extensive atrial amyloid infiltration and consequently blunted atrial function have been recently described by Bandera et al with ATTR-CM revealed augmented atrial stiffness and all the three components of the atrial functioning (reservoir, conduit and contraction) were significantly impaired.…”
Section: Echocardiographymentioning
confidence: 99%